1999
DOI: 10.1080/089106099435880
|View full text |Cite
|
Sign up to set email alerts
|

The Microbial Generation of Nitric Oxide in the Human Oral Cavity

Abstract: Nitric oxide a potent antimicrobial agent and vasodilator, may be synthesized in the human mouth due to the bacterial reduction of salivary nitrate. The purpose of this study was to determine whether intra-oral pH changes produced by the oral flora may augment the production of nitric oxide. To test this hypothesis a sucrose mouthrinse was administered to human volunteers who were free from caries and periodontal disease and production of oral nitric oxide was related to intra-oral pH changes. Baseline measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…The overall oral bacterial composition was consistent with previous literature, where Firmicutes, Actinobacteria, Bacteroidetes, Proteobacteria and Fusobacteria were the most abundant phyla [ 25 , 26 ]. This is further reflected at the family and genus levels, with Streptococcus , Prevotella , Neisseria and Haemophilus being most abundant genera [ 1 , 15 , 16 , 26 ].…”
Section: Discussionsupporting
confidence: 90%
“…The overall oral bacterial composition was consistent with previous literature, where Firmicutes, Actinobacteria, Bacteroidetes, Proteobacteria and Fusobacteria were the most abundant phyla [ 25 , 26 ]. This is further reflected at the family and genus levels, with Streptococcus , Prevotella , Neisseria and Haemophilus being most abundant genera [ 1 , 15 , 16 , 26 ].…”
Section: Discussionsupporting
confidence: 90%
“…The only genera of bacteria where the abundance changed significantly was Peptostreptoccocus which was more abundant in visit one compared to visit two (P=0.03). Previous research has shown that Peptostreptoccocus species do not have NO 3 reductase activity (Smith et al 1999).…”
Section: Abundance Of Nitrate-reducing Bacteriamentioning
confidence: 99%
“…In an early study, the estimated excretion of saliva by cattle during feed intake and remastication was between 98 and 190 L d -1 with four different diets (Bailey, 1961). Excretion of NO 3 via saliva could lead to intimate contact between dissolved NO 3 and degradable organic matter in the oral cavity where there is probably also a potential for inoculation with denitrifying organisms (Smith et al, 1999). Further research is needed to identify the mechanism and location of N 2 O formation.…”
Section: Mechanisms Behind Nitrous Oxide Emissionsmentioning
confidence: 99%